Influence of powdery mildew disease on sunflower and its possible management using Ampelomyces spp.: Influence of powdery mildew disease on sunflower and its possible management using Ampelomyces spp. - L RAJENDRAN; T SELVAKUMAR; R SASIKALA; P L VISWANATHAN (Journal of Oilseeds Research, 2020)
Among the different sunflower entries tested under artificial net-house conditions against powdery mildew disease, COSF 15 B showed highly susceptible reaction (HS) compared to CO 2 Hybrid (S), Sunbred 275 (S), Morden (HS) and CO 3 Hybrid (MR). Further, the entry recorded less mean seed volume weight (33.5 g/100 ml), oil content (33.5%) with a disease score of 9 under field conditions. An attempt has been made to isolate the naturally occurring mycoparasitic pycnidial fungi Ampelomyces spp. from powdery mildew infected leaves and four isolates were obtained. These isolated were slow growing on potato dextrose agar medium and produced pycnidia. These four isolates gave a 560 bp amplicon from the ITS region.